PENGARUH GAYA BELAJAR TERHADAP DISIPLIN ANAK DI TK ISLAM AL-MUHAJIRIN KELURAHAN SIMPANG PERAK JAYA KECAMATAN KERINCI KANAN KABUPATEN SIAK - Royani, Indah; Puspitasari, Enda; ', Wilson (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The background of this research is a discipline problem in children, the researchers found several children: do not pray before and after the study, did not ask permission out in learning, likes to talk loudly and shouting, no running in the class, do not want to put playground equipment on the shelves, no one spoke when the teacher was explaining, and no one can not sit neatly / silent when learning takes place even interfere with his friend who was working on a task. These actions indicate that there are children who do not obey the rules / regulations. The aim of this study was to determine the child's learning style and discipline as well as to determine the effect of learning styles to discipline children in kindergarten Islam Al-immigrants Perak Simpang Jaya village Right Kerinci District of Siak. The method used in this research is a quantitative study using correlation techniques. The sample used in this study were 48 children. The data collection techniques is done by observation. Based on the research results child's learning style more on visual learning style with a percentage of 60.5%, while the discipline of children classified into the category of being with a percentage of 79.1%. From the research that the correlation between the visual learning style with discipline is not significant and shows that the direction of a negative correlation with the strength of the correlation is very weak. Furthermore, the correlation between auditory learning style with discipline is not significant and shows that the direction of a positive correlation with the strength of the correlation is very weak. While the correlation between kinesthetic learning style with discipline are significant and show that the direction of a negative correlation with the strength of the correlation is weak. the overall results of this study showed no influence of learning style to child disclipine at islam al-muhajirin kindergarten in simpang perak jaya village kerinci kanan district siak regency This is evident from the results of Chi Square test.Keywords: learning style, discipline